Arthroscopic Medial Meniscal Root Repair Using a Novel Re-Tensionable All-Suture Anchor - Patrick Szukics DO; Jose Robaina MD; Jonas W. Ravich MS; Luis A. Vargas MD; Gautam Yagnik MD (SAGE Publishing, 2024)
Background: Medial meniscal root repairs are devastating injuries that can cause long-term knee problems if not properly addressed. Some common issues when addressing these injuries surgically include the "bungee-cord" effect seen with implants that sit too far from the tibial plateau surface and loss of tension on the sutures after cycling of the knee after the repair. This video will discuss the presentation of a patient with a medial meniscal root repair treated with a novel technique to counteract these aforementioned issues. Indications: Based on the patient's medial meniscal root tear and minimal arthritis seen on radiograph, he was indicated for a meniscal root repair to prevent meniscal extrusion and reinforce normal meniscal hoop stresses to limit progression of his arthritis. Technique Description: This technique uses a novel re-tensionable all-suture anchor through a transtibial tunnel with 2 repair sutures through the meniscal root that sits just below the tibial plateau, allowing the surgeon the ability to re-tension the implant after cycling the knee. Results: Arthroscopic repair of the medial meniscal root allowed the patient to return to his previous level of activity. Discussion/Conclusion: In this case, arthroscopic medial meniscal root repair can yield good results in patients to get them back to their previous level of activity while minimizing the chance of rapid arthritic progression that is typically seen with nonoperative management of these injuries. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.